Guidelines and quantitative standards to improve consistency in cetacean subspecies and species delimitation relying on molecular genetic data. (June 2017) - Taylor, Barbara L.; Archer, Frederick I.; Martien, Karen K.; Rosel, Patricia E.; Hancock‐Hanser, Brittany L.; Lang, Aimee R.; Leslie, Matthew S.; Mesnick, Sarah L.; Morin, Phillip A.; Pease, Victoria L.; Perrin, William F.; Robertson, Kelly M.; et al.
Abstract: Taxonomy is an imprecise science that delimits the evolutionary continuum into discrete categories. For marine mammals, this science is complicated by the relative lack of morphological data for taxa that inhabit remote and often vast ranges. We provide guidelines to promote consistency in studies relying primarily on molecular genetic data to delimit cetacean subspecies from both populations and species. These guidelines identify informational needs: basis for the taxonomic hypothesis being tested, description of current taxonomy, description of relevant life history, sample distribution, sample size, number and sequence length of genetic markers, description of measures taken to ensure data quality, summary statistics for the genetic markers, and analytical methods used to evaluate the genetic data. We propose an initial set of quantitative and qualitative standards based on the types of data and analytical methods most readily available at present. These standards are not expected to be rigidly applied. Rather, they are meant to encourage taxonomic arguments that are consistent and transparent. We hope professional societies, such as the Society for Marine Mammalogy, will adopt quantitative standards that evolve as new data types and analytical methods become widely available.